AUDIENCE'S ACCEPTANCE OF WOMEN'S SEXUAL OBJECTIVES IN THE FILM “SELESAI” (2021) - Ahmad, Namira Yunita; Tutiasri, Ririn Puspita; Clareta, Dyva; Arviani, Heidy (JOSAR (Journal of Students Academic Research), 2024)
This study aims to analyze the audience's reception of the sexual objectification of women in the film Finish (2021). This research method is a qualitative approach method. Data were obtained through in-depth interviews, documentation and literature studies. The results of the study showed that there were differences in interpretation of the acceptance of female sexual objectification in the film Finish (2021) by the informants. The meaning of informants is influenced by the background of each individual which is reproduced repeatedly in everyday life, or the frame of reference and field of experience of the informants. In line with Stuart Hall's reception analysis theory which refers to the encoding-decoding process. With reception analysis, it can be seen that the audience/viewers have an active role in interpreting the meaning in the film.